A note on pre-independence Negeri Sembilan through the lenses of federalism and constitutionalism - Mokhtar, Khairil Azmin (2019)
The Ancient Negeri Sembilan originally was a confederacy which had undergone three principal periods namely an early period and the four aborigine States; an intermediate period when these states were replaced by nine Minangkabau States; and a modern period during which four Minangkabau States formed themselves into an independent constitutional monarchy. The decentralization of powers in 1773 occurred when Raja Melewar was installed as the Sovereign of Negeri Sembilan. The decentralization of powers which was based on customary traditions manifested the effectiveness of the gradation of official powers in a territorial system and tribal organization. There was unity in diversity because Negeri Sembilan originally comprised of nine States based on its unique adat. They are populated by Minangkabau migration to the Peninsula and local people, who have developed their own socio-political institutions.